2003
DOI: 10.1007/s00421-003-0905-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of side dominance on myoelectric manifestations of muscle fatigue in the human upper trapezius muscle

Abstract: The purpose of this study was to investigate whether differences in the peripheral and control properties of the neuromuscular system due to long-term preferential use, related to side dominance, affect postural muscles, such as the upper trapezius. Therefore, fatigability properties of the upper trapezius muscles of the dominant and non-dominant side were assessed. Surface EMG signals were detected from the upper trapezius muscles of both sides of nine right- and five left-handed subjects with adhesive linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 40 publications
3
35
1
Order By: Relevance
“…No significant difference in EMG amplitude between RT and LT sides of upper trapizius in this current study might also attributed to overactivity of upper trapezius and levator scapula at one side can cause contralateral cervical rotation; in order to keep the head level and in a fixed position, the contralateral upper trapezius will become activated, so both upper trapezii will eventually become tight. This is agreed also with [25]. The results of this study also revealed that there was no significant difference in the EMG amplitude of gluteus maximus between RT and left sides.…”
Section: Discussionsupporting
confidence: 90%
“…No significant difference in EMG amplitude between RT and LT sides of upper trapizius in this current study might also attributed to overactivity of upper trapezius and levator scapula at one side can cause contralateral cervical rotation; in order to keep the head level and in a fixed position, the contralateral upper trapezius will become activated, so both upper trapezii will eventually become tight. This is agreed also with [25]. The results of this study also revealed that there was no significant difference in the EMG amplitude of gluteus maximus between RT and left sides.…”
Section: Discussionsupporting
confidence: 90%
“…All sessions were performed in a laboratory at a constant ambient temperature of 228C. The task was performed with both hands, but given that the dominant arm is more fatigue-resistant than the non-dominant arm (Farina et al 2003), electromyography, kinematics and PPT were only measured for the non-dominant side.…”
Section: Methodsmentioning
confidence: 99%
“…As handedness has been shown to have a significant impact in upper-extremity muscle activity, [14][15][16][17][18][19] the VRIs were All subjects were male (29 ± 4 years of age, 22-36 years of age). Mean height was 177.9 ± 9.3 cm and mean weight was 80.9 ± 8.1 kg.…”
Section: Subjects and Assessment Protocolmentioning
confidence: 99%